Horses, Mindfulness and the Natural Environment: Observations From a Qualitative Study with At-Risk Young People Participating in Therapeutic Horsemanship - Dr , Hannah Louise Burgon (International Journal of Psychosocial Rehabilitation, 2013)
The field of Equine-Assisted Learning and Equine-Assisted Therapy (EAL/T) where horses are co-facilitators in therapeut- ic and learning interventions claims to offer valuable benefits for young people and adults experiencing psychosocial diffi- culties. Some of the reported positive outcomes from participating in EAL/T include growths in self-confidence and self- esteem, increasing self-awareness and behaviour modification, building trust and attachment, and a host of other physical and mental health benefits. However, the area of how being with horses may enable participants to experience benefits from the natural environment together with aspects of mindfulness has received little attention. This paper is drawn from a qualitative, ethnographic, doctoral research study with seven “at-risk” young people aged between 11-21 years participat- ing in a Therapeutic Horsemanship programme in the UK. In addition to similar themes identified above the study found benefits related to the mindfulness and nature therapy literature. These included “being calm” and relaxation, being “in the moment”, psychospiritual aspects of “feeling free”, and links to theories of “emotion regulation” and “authentic function- ing” (Chambers et al. 2009; Heppner and Kernis 2007). The study has clinical implications to the fields of social work and psychotherapy as it suggests that horses may offer a valuable additional intervention for “at-risk” young people who may benefit from alternative therapeutic and learning experiences.